Effect of strategic intelligent games on gathering attention - Yesiltepe, Margrit; Altintas, Gulsen (E D P SCIENCES, 2016)
Nowadays, while raising the humans of information age, to which extent we can provide guidance under the roof of the school that will ensure them to tackle the problems that they will encounter in the future? Currently, to what extent do we assume our children whom we prepare for currently unknown professions of future ages the name, function and the requirements for equipment of which are not known by us now, for their future, country and the world will have what degree of strategic thinking skills and whether they will be attentive in case of confusion regarding the target. If we assume that the individuals who will keep pace with rapidly changing world and direct it should have very good level of attention, activities to improve it should be arranged. We should consider making foundations available for them to manage daily problems or possible obstacles by using different thinking methods and by managing them with the plans a, b even c prepared by them, and finding alternative responses in the competition environment and creating added value for them, their country and the world. For this purpose, increase in attention gathering level at the beginning of mental activities would positively affect this process. What would be the effect of plays in developing attention giving and gathering features that are not felt more until coming to the school age? Our study started with this question and the voluntarily participated students were observed during the study. Study covers 3 students playing at very low, middle and high frequency who are selected among universe of 10 students, 2 of which were girls who are the members of strategic mind games activities which is a working group indicating maximum diversity. Subject who are taken under the scope of the study are selected from upper socio-cultural level. Students were expected to participate in thinking skills developing paper-and-pencil activities and strategic mind games. Strategy developing games that are used in the study are used for development of gathering attention.
Keywords: Game; attention; Education & Educational Research